Conceptualizing Strategic Leadership: Theories, Themes, and Varying Perspectives - Chishamba, Jealous (Acta Universitatis Danubius. Œconomica, 2024)
Objectives: This paper conceptualizes strategic leadership (SL) by exploring foundational theories, central themes, and varying perspectives, emphasizing its role in aligning vision, setting strategic direction, and developing dynamic capabilities required for sustainable competitiveness. Prior Work: Building on the intersection of strategy and leadership theories, the paper integrates diverse frameworks addressing gaps in executive leadership literature, with theories like upper echelons, managerial cognition, and the resource-based view being central to the SL discourse. Approach: Employing a semi-systematic and integrative literature review, this paper critically examines SL through relevant theories, themes, and leadership perspectives, including top-down, collaborative, and distributed models. Results: SL is best operationalized through constructs emphasizing leaders’ cognitive abilities to develop mature strategic management processes, including determining direction, adapting to dynamic environments and managing core competencies. Implications: This study refines the understanding of SL as leadership “of” organizations rather than “in” organizations, offering insights for academics and strategic leaders on integrating strategic thinking across all levels to enhance strategic outcomes linked to key performance indicators (KPIs). Value: The paper presents a multidisciplinary SL framework, bridging theoretical insights and practical gaps, positioning SL as a catalyst for translating organizational strategy into sustainable competitive advantage (SCA)